A narrative review of digital screen time and sleep quality among young adults in India - Khan, Shiza; Siddiqui, Anwar; Husain, Fareha; Zubair, Mohammad Yasir (International Journal of Research in Medical Sciences, 2025)
In India, the digital revolution has transformed daily life patterns, with smartphone penetration and internet usage reaching historic levels. However, this digital transformation has raised significant concerns about adverse health effects, particularly regarding sleep quality. This narrative review synthesizes evidence from 30 studies published between 2010 and 2025 to explore the complex relationship between digital screen time and sleep quality among young adults aged 18–35 years in India. A comprehensive literature search was conducted across multiple databases including PubMed, Scopus, and Web of Science, and this review was synthesised. The findings reveal that young adults in India spend an average of 4–6 hours daily on digital devices, with smartphones accounting for the majority of screen exposure. Excessive screen time was consistently and significantly associated with multiple dimensions of sleep impairment, including delayed sleep onset, reduced sleep duration, poor overall sleep quality, and irregular sleep schedules. Notable gender differences emerged, with men more likely to engage in prolonged gaming sessions and women spending more time on social media, leading to distinct patterns of sleep disturbances. India-specific cultural and social factors, including academic pressure, professional demands, late-night entertainment consumption patterns, and social connectivity norms, further exacerbated the problem. The review concludes that excessive screen time represents a growing public health concern in India with implications extending beyond sleep to encompass mental health, academic and professional performance, and overall well-being.